2021
DOI: 10.3102/01623737211036728
|View full text |Cite
|
Sign up to set email alerts
|

Ready for College? Examining the Effectiveness of Targeted Interventions in High School

Abstract: Kentucky’s Targeted Interventions (TI) program is a statewide intervention intended to prepare non-college-ready high school students for college-level coursework. Using a difference-in-regression discontinuity design, we find that TI reduces the likelihood that students enroll in remedial courses by 8 to 10 percentage points in math. These effects are similar or stronger among students who are eligible for free/reduced-price lunch, students with remediation needs in multiple subjects, and students in lower pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…In addition to the usual assumptions of an RD—the existence of significant discontinuity in treatment receipt at the cutoff, the integrity of the running variable, no differential sample attrition at the cutoff—DiRD also assumes that the discontinuity in student outcomes at the cutoff due to college placement policies would have remained constant throughout the study period in the absence of TI. As demonstrated in Xu et al (2022), which uses the same identification approach we rely on here, there is no evidence that any of these assumptions are violated. The discontinuity in TI participation around ACT cutoffs is about 40 percentage points for both subjects.…”
Section: Data Measures and Methodsmentioning
confidence: 80%
See 4 more Smart Citations
“…In addition to the usual assumptions of an RD—the existence of significant discontinuity in treatment receipt at the cutoff, the integrity of the running variable, no differential sample attrition at the cutoff—DiRD also assumes that the discontinuity in student outcomes at the cutoff due to college placement policies would have remained constant throughout the study period in the absence of TI. As demonstrated in Xu et al (2022), which uses the same identification approach we rely on here, there is no evidence that any of these assumptions are violated. The discontinuity in TI participation around ACT cutoffs is about 40 percentage points for both subjects.…”
Section: Data Measures and Methodsmentioning
confidence: 80%
“…Consistent with the integrity of the running variable, key baseline covariates are continuous at the cutoff. Using student gender, race/ethnicity, and FRL eligibility as the outcome, Xu et al (2022) estimated the DiRD model as described above and found no detectable discontinuity at the cutoff except for the percentage of female students, where the difference is equivalent to about 0.10 standard deviation. Controlling for gender (as well as other covariates) in the DiRD model produces no meaningful change in estimated TI effects on college outcomes.…”
Section: Data Measures and Methodsmentioning
confidence: 99%
See 3 more Smart Citations